The spatial distribution of HO2 in an atmospheric pressure plasma jet investigated by cavity ring-down spectroscopy - Norman, HC; Ritchie, GAD (IOP Publishing, 2020)
Cold atmospheric pressure plasma jets make important contributions to a range of fields, such as materials processing and plasma medicine. In order to optimise the effect of those plasma sources, a detailed understanding of the chemical reaction networks is pivotal. However, the small diameter of plasma jets makes diagnostics challenging. A promising approach to obtain absolute number densities is the utilisation of cavity-enhanced absorption spectroscopy methods, by which line-of-sight averaged densities are determined. Here, we present first measurements on how the spatial distribution of HO2 in the effluent of a cold atmospheric pressure plasma jet can be obtained by cavity ring-down spectroscopy in an efficient way. Instead of recording fully wavelength resolved spectra, we will demonstrate that it is sufficient to measure the absorption coefficient at two wavelengths, corresponding to the laser being on and off the molecular resonance. By sampling the effluent from the 1.6 mm diameter nozzle in the radial direction at various axial positions, we determined that the distances over which the HO2 density was distributed were (3.9 ± 0.5) mm and (6.7 ± 0.1) mm at a distance of 2 mm and 10 mm below the nozzle of the plasma jet, respectively. We performed an Abel inversion in order to obtain the spatial distribution of HO2 that is presented along the symmetry axis of the effluent. Based on that localised density, which was (4.8 ± 0.6)centerdot 1014 cm-3 at the maximum, we will discuss the importance of the plasma zone for the production of HO2.